2021
DOI: 10.1111/mve.12518
|View full text |Cite
|
Sign up to set email alerts
|

Climate and the seasonal abundance of the tick Dermacentor reticulatus

Abstract: Dermacentor reticulatus (Ixodida: Ixodidae, Fabricius 1794) is one of the most widely distributed and abundant tick species in central Europe and is a vector for a range of pathogens. Nevertheless, many aspects of its ecology and distribution remain poorly understood. To quantify the seasonal abundance of this species in the U.K. and the environmental factors that determine this, weekly sampling at sites throughout Wales and southern England was undertaken for 12 months. This showed that the activity of adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The changes in mortality probability with temperature and RH indicated that the areas with high temperature and low RH are less suitable for tick survival, while ticks in areas with low temperature and high RH can have a relatively longer survival time. Similar patterns have been observed in Rhipicephalus ( Boophilus ) annulatus (Say) larvae 18 and Dermacentor reticulatus Fabricius 19 . Previous studies have demonstrated that water balance is crucial for tick survival 6,7 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The changes in mortality probability with temperature and RH indicated that the areas with high temperature and low RH are less suitable for tick survival, while ticks in areas with low temperature and high RH can have a relatively longer survival time. Similar patterns have been observed in Rhipicephalus ( Boophilus ) annulatus (Say) larvae 18 and Dermacentor reticulatus Fabricius 19 . Previous studies have demonstrated that water balance is crucial for tick survival 6,7 .…”
Section: Discussionsupporting
confidence: 75%
“…Similar patterns have been observed in Rhipicephalus (Boophilus) annulatus (Say) larvae 18 and Dermacentor reticulatus Fabricius. 19 Previous studies have demonstrated that water balance is crucial for tick survival. 6,7 All parasitic life stages of Rhipicephalus sanguineus s.l.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal course of the citizens' tick collections confirm the bimodal activity pattern of both tick species ( 38 , 57 , 58 ). In contrast to the year 2019, when most of the received D. reticulatus specimens were collected in September ( 10 ), collection of this species was more evenly spread between the months of September, October and November 2020, which may be due to year-to-year variation of climatic conditions.…”
Section: Discussionsupporting
confidence: 60%
“…From the Bioclim dataset, a subset of variables were chosen based on their ecological relevance to Dermacentor spp. ( 37 , 38 ). usdm::vifstep ( 39 ) was used to exclude variables with a variance inflation factor (VIF) exceeding 10, which indicates collinearity ( 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesize that this association between higher saturation deficits in the warmer months and an increase in the abundance of larval and female B. hydrosauri in August to December is due to a relationship between climate and the host‐seeking of B. hydrosauri . Studies of other ixodid ticks, have revealed an intricate relationship between the host‐seeking activity of ticks and saturation deficit; that higher saturation deficits result in lower host‐seeking (Perret et al, 2000; Randolph & Storey, 1999; Sands et al, 2021; Zajac et al, 2021). We hypothesize that this relationship between saturation deficit and host‐seeking activity is true for B. hydrosauri as well.…”
Section: Discussionmentioning
confidence: 99%